Applications of Bacterial Degrons and Degraders — Toward Targeted Protein Degradation in Bacteria - Izert, Matylda Anna; Klimecka, Maria Magdalena; Górna, Maria Wiktoria (Frontiers in Molecular Biosciences, 2021)
A repertoire of proteolysis-targeting signals known as degrons is a necessary component of protein homeostasis in every living cell. In bacteria, degrons can be used in place of chemical genetics approaches to interrogate and control protein function. Here, we provide a comprehensive review of synthetic applications of degrons in targeted proteolysis in bacteria. We describe recent advances ranging from large screens employing tunable degradation systems and orthogonal degrons, to sophisticated tools and sensors for imaging. Based on the success of proteolysis-targeting chimeras as an emerging paradigm in cancer drug discovery, we discuss perspectives on using bacterial degraders for studying protein function and as novel antimicrobials.